Correlations of conductance peaks and transmission phases in deformed quantum dots - Baltin, Reinhard; Gefen, Y.; Hackenbroich, Gregor; Weidenmüller, Hans-Arwed (The European physical journal. B, Condensed matter and complex systems, 1999)
We investigate the Coulomb blockade resonances and the phase of the transmission amplitude of a deformed ballistic quantum dot weakly coupled to leads. We show that preferred single-particle levels exist which stay close to the Fermi energy for a wide range of values of the gate voltage. These states give rise to sequences of Coulomb blockade resonances with correlated peak heights and transmission phases. The correlation of the peak heights becomes stronger with increasing temperature. The phase of the transmission amplitude shows lapses by π between the resonances. Implications for recent experiments on ballistic quantum dots are discussed.